Metaphor universals in literature - Kövecses (ELTE-Budapest), Zoltán (ANTARES: Letras e Humanidades, 2018)
In the paper, I address the issue of metaphor universals in poetry only – leaving aside the genre of the novel. This decision is the result of practical considerations, rather than any theoretical reasons. Within the framework of conceptual metaphor theory, a lot more work has been done on poetry than on the novel, probably mostly because a pioneering study on metaphor by Lakoff and Turner (1989) also focused on poetry. Conceptual metaphor consists of a set of systematic mappings between two domains of experience (LAKOFF; JOHNSON, 1980). One domain, which is typically more abstract, is called the target domain, and the other, which is typically more concrete or physical, is called the source domain. The more concrete domain is used to understand the more abstract one. A conceptual metaphor can have a variety of different manifestations in various modalities, including linguistic manifestations.